The Role of Communication, Motivation, and Leadership in Employee Performance at Padma Resort Legian: Peran Komunikasi, Motivasi, dan Kepemimpinan terhadap Kinerja Karyawan Padma Resort Legian - Sunbanu, Putu Juvan Holy Christin; Utama, I Gusti Bagus Rai; Adinegara, Gusti Ngurah Joko (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2025)
This study investigates the influence of communication, motivation, and leadership on employee performance at Padma Resort Legian, a tourism-based hospitality company where employee performance is crucial to service quality. The research aims to determine both partial and simultaneous effects of these variables on performance. Employing a quantitative associative approach, the study used a purposive sampling method with 76 respondents. Data were collected through questionnaires and analysed using SPSS 26 for Windows, applying validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and determination coefficient analysis. The results reveal that communication (X₁) positively and significantly affects employee performance (b₁ = 0.231; count = 2.319 > t_table = 1.993). Motivation (X₂) also has a positive and significant effect (b₂ = 0.411; t_count = 4.512 > t_table = 1.993), as does leadership (X₃) (b₃ = 0.198; t_count = 2.622 > t_table = 1.993). Simultaneously, the three variables significantly influence performance (F_count = 62.260 > F_table = 2.73; p < 0.05), with an R² value of 0.722, indicating that they account for 72.2% of the variance in performance. It is concluded that effective communication, high motivation, and strong leadership are critical to enhancing employee performance at Padma Resort Legian. The study recommends management prioritise employee development programs that strengthen interpersonal communication, foster motivation through recognition and incentives, and encourage transformational leadership practices to sustain service excellence.